Time-Dependent Trapping of Pollinators Driven by the Alignment of Floral Phenology with Insect Circadian Rhythms - Lau, Jenny Y. Y.; Guo, Xing; Pang, Chun-Chiu; Tang, Chin Cheung; Thomas, Daniel C.; Saunders, Richard M. K. (Frontiers in Plant Science, 2017)
Several evolutionary lineages in the early-divergent angiosperm family Annonaceae possess flowers with a distinctive pollinator trapping mechanism, in which floral phenological events are very precisely timed in relation with pollinator activity patterns. This contrasts with previously described angiosperm pollinator traps, which predominantly function as pitfall traps. We assess the circadian rhythms of pollinators independently of their interactions with flowers, and correlate these data with detailed assessments of floral phenology. We reveal a close temporal alignment between patterns of pollinator activity and the floral phenology driving the trapping mechanism (termed ‘circadian trapping’ here). Non-trapping species with anthesis of standard duration (c. 48 h) cannot be pollinated effectively by pollinators with a morning-unimodal activity pattern; non-trapping species with abbreviated anthesis (23–27 h) face limitations in utilising pollinators with a bimodal circadian activity; whereas species that trap pollinators (all with short anthesis) can utilise a broader range of potential pollinators, including those with both unimodal and bimodal circadian rhythms. In addition to broadening the range of potential pollinators based on their activity patterns, circadian trapping endows other selective advantages, including the possibility of an extended staminate phase to promote pollen deposition, and enhanced interfloral movement of pollinators. The relevance of the alignment of floral phenological changes with peaks in pollinator activity is furthermore evaluated for pitfall trap pollination systems.